Performance Obstacles and Workload of Nurses Working in Critical Care Unit at Teaching Hospital - Poudyal, Sunita; Sharma, Kalpana; K.C., Soni (Journal of Karnali Academy of Health Sciences, 2023)
Background: Performance obstacles are the elements of immediate workplace that restrict nurses’ capacity to perform their duties. Performance obstacles are significant predictor of nurses’ workload, which lowers their satisfaction and, in turn, affects their quality of work life. This study aimed to assess the performance obstacles and workload of nurses working in critical care unit.Methods: The descriptive cross-sectional study was carried out among all the 103 nurses working in critical units of selected hospital. Non-probability total enumerative sampling technique was used. Data were collected using self-administered questionnaire from 5th March 2023 to 5th April 2023. Data were analyzed in SPSS version 15 using descriptive statistics for the description of variables, and Spearmann correlation coefficient was calculated to measure the relationship between variables.Results: Study revealed that, among the four domains of obstacles, nurses experienced higher performance obstacles in task domain (50.0%), followed by work environment (37.5%), whereas lowest in organization domain (28.5%). The median overall performance obstacle score reported by nurses was 36%. There was positive correlation between performance obstacles related to tasks with workload domains of mental demand (r=0.257, p=0.009), physical demand (r=0.258, p=0.009), temporal demand (r=0.212, p=0.031) and efforts (r=0.250, p=0.011). Likewise, performance obstacles related to organization was positively correlated with mental demand (r=0.236, p=0.017), physical demand (r=0.246, p=0.012), temporal demand (r=0.361, p